The Use of Machine Learning for the Detection and Analysis of Brain Cancer in Imaging - Ahamed, Shaik Masood; Jabez, J. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Brain tumors can develop when cell division proceeds rapidly and unchecked. There is a risk of death if it is not diagnosed and treated in time. Accurate segmentation and classification remains difficult despite multiple important efforts and promising improvements in this sector. Brain tumors are notoriously difficult to diagnose because of their highly variable sizes, shapes, and locations. The goal of this research was to provide academics with a thorough literature on MRI for the diagnosis of brain malignancies. The basics of brain tumors, where to find public datasets, how to enhance them, how to segment them, how to extract features to categorize them, and how to apply deep learning, quantum machine learning and transfer learning to analyze them were all discussed in this overview.